Sources of Agricultural Information Used by Arable Crop Farmers in Isale Osun Farm Settlement, Osogbo Local Government Area of Osun State - A E Agwu; A A Adeniran (Journal of Agricultural Extension, 2009)
The study ascertained the sources of agricultural information used by arable crop farmers in Isale Osun farm settlement, Osogbo local government area of Osun State. Data were collected from 80 respondents through the use of structured interview schedule and analyzed using percentages, mean scores and bivalent correlation analysis. The findings revealed that farmers received their agricultural information mostly through mediated and professional inter-personal channels/methods. The findings further showed that radio ( farmers ( x = 3.40) and fellow x = 3.40) were the most perceived appropriate channels for disseminating agricultural information as reported by the farmers. However, the result of the study showed that extension agents ( x = 3.37), radio ( and television ( x = 3.34) x = 3.16) were the most reliable channels for communicating agricultural information to farmers. The results of the bivalent correlation analysis showed positive significant relationships between educational attainment and Â use of professional information sources; farmersâ€™ age and use of various information sources as well as household size and use of professional mass media sources (P<0.05).However, level of illiteracy ( x = 3.97), unavailability of information sources ( x = 3.94), lack of access to information sources ( 3.93) and inappropriate scheduling of programmes ( x = x = 3.89) were the most serious problems associated with receiving information through the different communication sources. The study therefore recommended that government should assist farmers in the area by sponsoring adult education so that farmers can make best use of the different agricultural information sources effectively. It also points to the need for the provision of enabling environment for such facilities as the internet to thrive in rural areas